Consequential life cycle assessment of bamboo leaf ash generation: A Brazilian context - Sposito, C. C.A. (2024)
The potential of biomass growth, such as from bamboo leaves, as a source of electricity provides an optimistic scenario for the sustainable development of new green building materials. To validate robust life cycle inventory (LCI) data for incoming high-quality silica sources for cementitious materials, a consequential life cycle assessment (CLCA) on the bamboo leaves ash (BLA) with a prospective approach was conducted. The LCI data was collected in Southeastern Brazil with a prospective maturity in biomass electricity system. The data was gathered by analyzing the various stages involved in the production of BLA, including bamboo cultivation, leaf collection, cogeneration, raw BLA beneficiation, and its impact on cement and electricity marginal production systems. According to the multifunctionality solution, the environmental impacts results of CLCA were discussed using a sensibility analysis with two attributional life cycle assessment (ALCA) scenarios as allocation and “zero environmental load” (considering BLA as residue). The scenarios demonstrate the potential for sustainable use of BLA, especially for its impact on climate change, including the biogenic carbon category. Also, consequences such as avoiding BLA landfilling and increasing the potential for bamboo agricultural holdings to become energy independent was included in the study conclusion. While these results are positive, the prospect of maturing electricity production requires the development of other high-quality materials, such as sugarcane bagasse ash, sugarcane leaf ash and rice husk ash. However, the positives consequences did not overcome the negative impacts from the transportation of BLA into its system boundaries, once the highway transport model is the manly in the Brazilian context. Hence, this study provides important and reproducible pathways for developing LCI data on other biomass ashes, assisting future studies on green building materials.